A study of Politness Strategies in the Conversational Activities of the course book “New English File – Intermediate = Nghiên cứu về chiến lược lịch sự trong các bài hội thoại của giáo trình giao tiếp “New English File. M.A Thesis Linguistics: 60 22 15 - Phạm, Thị Hồng Liên (University of Languages and International Studies, 2017)
38 p. + CD-ROM